(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores the effectiveness and user preferences of digital versus print resources in enhancing comprehension, retention, and overall academic performance among library users. The research involved 300 participants with diverse demographic backgrounds, including a nearly equal gender distribution and a range of age groups, educational levels, and fields of study. The study employed independent samples t-tests to compare the performance of digital and print resources across key academic metrics. The findings reveal that print resources consistently outperform digital resources in terms of comprehension, retention, and academic performance, with statistically significant differences observed (p < 0.05). Specifically, print materials are particularly effective for deep reading and tasks requiring sustained focus, as evidenced by higher satisfaction and perceived effectiveness ratings. Conversely, digital resources are more frequently utilized, especially for research purposes, reflecting their convenience and accessibility. The study underscores the importance of maintaining a balanced collection of both digital and print resources in libraries to cater to the diverse needs and preferences of users. While digital resources are indispensable for research and frequent use, print materials remain crucial for achieving higher academic outcomes in tasks that demand deep engagement. The research highlights the need for libraries to enhance the effectiveness of digital resources while continuing to promote the unique advantages of print materials. By doing so, libraries can better support the academic success and satisfaction of their users, ensuring they meet the evolving demands of the modern learning environment.